LITHIUM BLEND FITTING FOR roAp STAR HD101065 (PRZYBYLSKI’S STAR) - Shavrina, A. V.; Khalack, V.; Polosukhina, N. S.; Zverko, J.; Zhiznovsky, J.; Gopka, V. F.; North, P.; Tsymbal, V. V.; Yushchenko, A. V. (Одеські астрономічні публікації, 2017)
We have considered the possibility for modeling of remarkable spectral feature 6708 Å for HD101065 (Przybylski’s star) in two ways - as a blend of Li and REE lines and as blend of REE lines only. We show by model calculations that Li lines absorb significantly in the range 6707.72-6708.02 ÅÅ and resulting Li abundance 3.3 dex (in the scale lg N(H)=12.0) is near to the primordial value.